2015
DOI: 10.1016/j.infbeh.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preterm birth on infant negative affect and maternal postpartum depressive symptoms: A preliminary examination in an underrepresented minority sample

Abstract: Objective To examine the effect of preterm birth on maternal postpartum depressive symptoms and infant negative affect in an underrepresented minority sample. Method Participants were 102 mothers and their 3- to 10-month-old infants. Mothers completed the Edinburgh Postnatal Depression Scale and the Infant Behavior Questionnaire-Revised. Results Relative to normative samples, the current underrepresented minority sample of mostly Hispanics and Blacks displayed high rates of preterm birth (30%) and maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
5
14
0
2
Order By: Relevance
“…A careful review of the literature indicates that medical complications occurring during pregnancy and/or childbirth have been inconsistently linked to postpartum psychiatric disorders (Blom et al 2010). These include complications of pregnancy such as pre-eclampsia (Steegers et al 2010; Robillard et al 2011; Di Florio et al 2014; Munk-Olsen et al 2014), hyperemesis gravidarum (HG; severe nausea and vomiting) (Poursharif et al 2008; Buyukkayaci Duman et al 2015), gestational diabetes (Nicklas et al 2013; Barakat et al 2014; Ferrara et al 2014; Meltzer-Brody & Stuebe, 2014) and gestational hypertension (Bijlenga et al 2011; Rigó et al 2015), as well as obstetrical complications including postpartum hemorrhage (Sentilhes et al 2011; Thompson et al 2011), Cesarean section (C-section) (Hannah et al 2004; Sword et al 2011; Houston et al 2015) and preterm birth (Grigoriadis et al 2013; Barroso et al 2015; Helle et al 2015). These pregnancy and obstetrical complications occur relatively commonly: The prevalence of pre-eclampsia is 5–8% of all pregnancies (Leffert, 2015), preterm birth is about 10% (Delnord et al 2015; Horgan, 2015) and gestational diabetes is up to 9% (DeSisto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A careful review of the literature indicates that medical complications occurring during pregnancy and/or childbirth have been inconsistently linked to postpartum psychiatric disorders (Blom et al 2010). These include complications of pregnancy such as pre-eclampsia (Steegers et al 2010; Robillard et al 2011; Di Florio et al 2014; Munk-Olsen et al 2014), hyperemesis gravidarum (HG; severe nausea and vomiting) (Poursharif et al 2008; Buyukkayaci Duman et al 2015), gestational diabetes (Nicklas et al 2013; Barakat et al 2014; Ferrara et al 2014; Meltzer-Brody & Stuebe, 2014) and gestational hypertension (Bijlenga et al 2011; Rigó et al 2015), as well as obstetrical complications including postpartum hemorrhage (Sentilhes et al 2011; Thompson et al 2011), Cesarean section (C-section) (Hannah et al 2004; Sword et al 2011; Houston et al 2015) and preterm birth (Grigoriadis et al 2013; Barroso et al 2015; Helle et al 2015). These pregnancy and obstetrical complications occur relatively commonly: The prevalence of pre-eclampsia is 5–8% of all pregnancies (Leffert, 2015), preterm birth is about 10% (Delnord et al 2015; Horgan, 2015) and gestational diabetes is up to 9% (DeSisto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Poor birth outcomes such as preterm birth have been reported to increase the risk of postpartum depressive symptoms in women [ 5 7 ]. O'brien et al, in a longitudinal study on maternal depression following premature birth, reported that almost half the mothers of premature infants reported depressive symptoms during hospitalization, at discharge, and six weeks after discharge [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Screening scores positive for stress and depression were associated with a negative change in some infant development scores and maternal quality of life scores. While studies have examined the impact of maternal mental health on the mother and fetus [ 31 ], few have examined the prevalence of PTSD and depression after NICU discharge in a diverse and underserved population as presented [ 32 ].…”
Section: Discussionmentioning
confidence: 99%